Desenvolvimento e comparação de métodos em cromatografia líquida mono e bidimensional abrangente (LC×LC), utilizando ferramentas quimiométricas para análise de folhas de Casearia sylvestris - Correia, Lilian Cherubin [UNESP] (2016)
Bidimensional liquid chromatographic separations have attracted intense interest over the past decade based on the potential improvements in resolving power they offer for analysis of complex samples. Despite the use of orthogonal columns and the theoretical multiplication of peak capacity from both dimensions, one question remains: “Are bidimensional techniques superior to monodimensional ones for analysis of vegetal extracts?”. This question led to the purpose of the present work, that was to compare the performance between LC and LC×LC, using leaves from Casearia sylvestris, a widely used tree in Brazilian folk medicine by its biological activities. Furthermore, due to the large volume of waste generated by LC, the replacement of conventional solvents by ethanol (EtOH), a less toxic and biodegradable alternative solvent was chosen. The most challenging issue of any multidimensional chromatography is the method development, since the large number of interacting parameters that must work together in a single run. Two strategies for method development were used in this work. The first one was divided into 4 steps: experiments were carried out to select the most orthogonal pair of columns, 1D method development using design of experiments, another design of experiments for 2D conditions was proposed (2tc, modulation time and tre, re-equilibration time after each modulation) and aware of the best conditions for both dimensions, 2D gradient types were evaluated. The second strategy consisted of selecting the most orthogonal pair of columns, optimization of both dimensions simultaneously by design of experiments and finally evaluation of 2D gradient type. Both strategies were efficient for comprehensive bidimensional method development, but the second one was found to be faster, due to the lesser number of required experiments. Nevertheless, using ethanol as mobile phase proved to be impractical for fast and high flow rates analysis of 2D due to its high viscosity and its use as mobile phase was rejected. Finally, a comparison between the fully optimized bidimensional chromatographic method and two 1D-LC methods previously described in the literature for C. sylvestris were made. Using peak capacity as a metric of comparison, a higher performance was achieved for LC×LC. This study concluded that LC×LC provides a higher performance than 1D-LC, however, its use will depend of the analysis purpose because this gain in performance was achieved with longer analysis times (approximately 4x) and greater generation of residues (approximately 30x), or technological improvements.